Relationship Between Runoff Coefficient and Curve Number for Sungai Weng and Sungai Kayu Ara Catchments - Ishak, Asnor Muizan (2006)
Traditionally, the rational formula that embodies runoff coefficient in the equation has widely been used for drainage design due to its simplicity. Two widely used design manuals that are particularly related to the rational formula in Malaysia are the Hydrological Procedure No. 16 (HP16) - Flood Estimation for Urban Areas in Peninsular Malaysia and Hydrological Procedure No. 5 (HP5) - Rational Method of Flood Estimation for Rural Catchments in Peninsular Malaysia. The latter presents the runoff coefficient that have been derived using the statistical approach rather than the deterministic, however, the former shows the look-up table of runoff coefficients that are adopted from few previous efforts that were carried out by some local authorities. The HP16 however has been superceded by the Urban Stormwater Management Manual (MSMA) in 2001, but the runoff coefficients proposed in the manual have been directly adopted from Australian practice. This study attempts primarily to derive runoff coefficient and runoff curve number in two small catchments [1] urban catchment of Sungai Kayu Ara (more than 48.81% urbanized), and [2] forest catchment of Sungai Weng by using the deterministic approach. The other popular method that is widely used in hydrology is the Soil Conservation Services (SCS) method, which uses runoff curve number (CN), which has several advantages against the rational method partly because of its flexibility in generating flood hydrograph. In this study, the primary objective was to formulate the relationship between the runoff coefficient (C) and runoff curve number (CN) such that the coefficients can be easily determined for catchments of similar characteristics. The results show that the runoff coefficient and runoff curve number from the forest catchment were in the range of 0.05 to 0.30 and 44 to 64 respectively; for the urban catchment it was found to be in the range of 0.30 to 0.65 and 64 to 97. The average C for the forest and urban catchments were 0.13 and 0.55 respectively; while the average CN were about 52 and 83 respectively. There was no linear relationship between the two coefficients; however the relationship has been established using logarithmic fit which results in the correlation coefficient, r= 0.54 and 0.78 for the forest and urban catchment respectively. Runoff coefficients calculated using the relationship proposed by Chen have been compared with the values obtained in this study. The results show a good agreement for the forest catchment but a slightly poorer agreement in the urban catchment. The SCS initial abstraction factor (K) and peaking factor (F) are also determined in this study.